2013
DOI: 10.1002/path.4235
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of type I interferon signalling prevents TLR ligand-mediated proteinuria

Abstract: The mechanisms by which inflammation or autoimmunity causes proteinuric kidney disease remain elusive. Yet proteinuria is a hallmark and a prognostic indicator of kidney disease, and also an independent risk factor for cardiovascular morbidity and mortality. Podocytes are an integral component of the kidney filtration barrier and podocyte injury leads to proteinuria. Here we show that podocytes, which receive signals from the vascular space including circulating antigens, constitutively express TLR1–6 and TLR8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 49 publications
2
20
0
Order By: Relevance
“…At the level of histology, glomerular damage was more significantly suppressed relative to tubulointerstitial and tubular end points. In addition to expression on infiltrating lymphoid and myeloid cells, TLRs are expressed by several kidney-resident cell populations, including podocytes (33). These cells may respond to any damage-associated molecular pattern molecules released in response to tissue damage (34).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the level of histology, glomerular damage was more significantly suppressed relative to tubulointerstitial and tubular end points. In addition to expression on infiltrating lymphoid and myeloid cells, TLRs are expressed by several kidney-resident cell populations, including podocytes (33). These cells may respond to any damage-associated molecular pattern molecules released in response to tissue damage (34).…”
Section: Discussionmentioning
confidence: 99%
“…BMS-986126 was also tested against a panel of 338 kinase assays using 33 P incorporation at Reaction Biology (Malvern, PA). Each kinase was tested individually in duplicate with 1 mM BMS-986126 and 10 mM ATP.…”
Section: Kinase Assaysmentioning
confidence: 99%
“…Additional cell type-specific effects include the upregulation of adhesion molecules, increased vascular permeability in renal endothelial cells, and filtration barrier dysfunction in podocytes. [89][90][91][92][93] Resident and infiltrating mononuclear phagocytes also host the NLRP3 inflammasome that integrates DAMP signals such as ATP, histones, HA, biglycan, crystals, or uromodulin into the activation of caspase-1. 81,[94][95][96][97] Caspase-1 and caspase-11 confer proteolytic cleavage of pro-IL1b and pro-IL-18 into the mature cytokines, which are then secreted and trigger local inflammation inside the kidney (reviewed in ref.…”
Section: Damp Effects On Kidney Injury and Repairmentioning
confidence: 99%
“…Gurkan and colleagues recently showed that podocytes, which receive signals from the vascular space, including circulating antigens, constitutively express TLR1–6 and TLR8 [18]. They additionally found that podocytes can respond to TLR ligands including staphylococcal enterotoxin, poly I:C, or lipopolysaccharide with pro-inflammatory cytokine release and activation of type I interferon signaling [18]. This induced podocyte CD80 expression, and transient proteinuria, which could be blocked by a type I interferon receptor-blocking antibody [18].…”
Section: How Does Cd80 Targeted Therapy Work In the Podocyte?mentioning
confidence: 99%
“…They additionally found that podocytes can respond to TLR ligands including staphylococcal enterotoxin, poly I:C, or lipopolysaccharide with pro-inflammatory cytokine release and activation of type I interferon signaling [18]. This induced podocyte CD80 expression, and transient proteinuria, which could be blocked by a type I interferon receptor-blocking antibody [18]. This study significantly extended our understanding of podocyte responses to immune stimuli and revealed a novel mechanism for infection- or inflammation-induced proteinuria in a CD80-dependent, T-cell independent manner.…”
Section: How Does Cd80 Targeted Therapy Work In the Podocyte?mentioning
confidence: 99%